Perception, attitude, and practice of labor analgesia among obstetric care providers in Eastern Uttar Pradesh - Imran Ahmed Khan; Vani Aditya; Arun Kumar Srivastava; DK Srivastava (Asian Journal of Medical Sciences, 2023)
Background: Labor pain is among the foremost severe pain that ladies experience in their lifespan, if inadequately treated can lead to certain complications in labor. Relieving this pain with medical interventions is also full of misconceptions and disagreement among people. Different traditional and pharmacological methods for labor pain relief are utilized by obstetric care providers.